Analysing macro-poverty linkages: an overview - Gunter, Bernhard G.; Cohen, Marc J.; Lofgren, Hans (Wiley, 2005)
The analysis of macro-poverty linkages has emerged as an important but contentious area of national and international policy-making. Over the last few years, considerable progress has been made in understanding the linkages between macroeconomic policies and poverty reduction, as well as in developing evaluation tools and methodologies useful in conducting ex-ante PSIAs of macro policies. Nevertheless, while there are some reasons for optimism about the future, the potential contribution of these insights and tools to poverty reduction is largely unfulfilled. This article provides an introduction to this theme issue on 'Analysing Macro-Poverty Linkages' by reviewing (i) macroeconomic policy debates and (ii) methods and tools for evaluating the impact of macro policies on poverty.